Pengaruh Plyometric Split Jump dan Double Leg Speed Hop Terhadap Kecepatan Tendangan Lurus (Universitas Negeri Semarang, 2022)
Pencak silat was an original Indonesian cultural art that has a deep meaning that involved physical and mental movements. Physical movement included techniques, one of which was a straight kick technique which was still not optimized for speed and correct straight kicks. This type of research was quantitative with a quasi-experimental method. The research design was a two group pretest-posttest design. The subject was the male pencak silat athlete at SMP 3 Blora. The sampling technique was total sampling. Data analysis used validity test, normality test, homogeneity test and hypothesis test: paired sample t test. Based on the paired sample t test, the mean values ​​were -9.067 and -8.370, meaning that there was an increase in the speed of straight kicks for male pencak silat athletes at SMP 3 Blora after being given treatment. Then it was concluded that there was an effect of plyometric split jump on the speed of straight kicks and there was an effect of plyometric double leg speed hop on the speed of straight kicks.